Depression. Issue 3 (June 2015) - Schulz, Paul E.; Arora, Garima
Abstract : Purpose of Review: : Depression is a presenting symptom of common psychiatric disorders such as major depressive disorder, bipolar disorder, and schizophrenia. Depression can also be the presenting symptom of several neurodegenerative disorders, including Alzheimer disease, dementia with Lewy bodies, frontotemporal dementia, and Parkinson disease. Depression can also cause cognitive impairment and is a risk factor for dementia. As a result of the intimate relationship between depression and dementia, differentiating between a psychiatric and a neurologic cause of depression and dementia can sometimes be very difficult. The purpose of this review is to discuss the diagnosis and treatment of depression and to demonstrate how new diagnostic tools are helping to identify the differential diagnosis of depression. Recent Findings: : It is a time of great advancement in the management of depression. Innovative new medications, psychotherapeutic modalities, and new and investigational somatic treatments (eg, transcranial magnetic stimulation, deep brain stimulation) are making it possible to ameliorate and manage symptoms more effectively in more patients. Summary: : With our greater ability to improve the lives of patients with depression, it is important for neurologists to recognize depression and work with our psychiatric colleagues to help patients access the newest and best treatments.